Boosting carbon quantum dots/fullerene electron transfer via surface group engineering. Issue 45 (8th November 2016) - Privitera, Alberto; Righetto, Marcello; Mosconi, Dario; Lorandi, Francesca; Isse, Abdirisak A.; Moretto, Alessandro; Bozio, Renato; Ferrante, Camilla; Franco, Lorenzo
Abstract : Thiophene functionalization of N-doped carbon quantum dots greatly increases their electron donating capabilities under visible light excitation. Abstract : The design of novel nanostructures with tailored opto-electronic properties is a crucial step for third-generation photovoltaics, and the development of cheap and environmentally compatible materials is still a challenge. Carbon quantum dots (CQDs) emerged as promising candidates but usually a low processability and poor electron-donor properties hampered their photovoltaic applications. We tackle these issues through the synthesis and photophysical characterization of N-doped CQDs functionalized with different thiophene-containing groups. Functionalization was aimed at enhancing the electron donating properties of the carbon dots and improving the solubility in nonpolar solvents. The increased solubility in organic solvents allowed us to investigate the photoinduced interactions of the functionalized carbon dots with the fullerene derivative PCBM in solution and in solid blends. The investigation was carried out by cyclic voltammetry, photoluminescence spectroscopy and electron paramagnetic resonance (EPR). The remarkable oxidation potential shift of the functionalized carbon dots with respect to the pristine materials and the HOMO–LUMO energies strongly suggest them as good electron donors towards PCBM. The electron transfer process between CQDs and PCBM resulted in efficient fluorescence quenching in solution and in total quenching in solid blends. By using EPR spectroscopy in the solid blends, we demonstrated the efficient electron transfer by observing the photoinduced formation of a PCBM radical anion in the presence of functionalized CQDs. Time-resolved EPR allowed us to identify differences in the charge transport efficiency for different CQD:PCBM blends. The enhanced processability of CQDs with PCBM and the promising charge-generation and separation properties pave the way to the development of "all-carbon" photovoltaic devices.